Unravelling liberal interventionism local critiques of statebuilding in Kosovo - Visoka, Gëzim; Musliu, Vjosa 1985- (Worlding beyond the West, 2019)
Despite calls for the decolonisation of knowledge, scholars who come from conflict-affected societies remained marginalised, excluded from the examination of the politics and impacts of liberal interventionism. This edited volume gives local scholars a platform from which they critically examine different aspects of liberal interventionism and statebuilding in Kosovo. Drawing on situational epistemologies and grounded approaches, the chapters in this book interrogate a wide range of themes, including: the politics of local resistance; the uneven relationship between international statebuilders and local subjects; faking of local ownership of security sector reform and the rule of law; heuristic and practical limits of interventionism, as well as the subjugated voices in statebuilding process, such as minorities and women. The book finds that the local is not antidote to the liberal, and that local perspectives are not monolithic. Yet, local critiques of statebuilding do not seek to generate replicable knowledge; rather they prefer generating situational and context-specific knowledge be that to resolve problems or uncover the unresolved problems. The book seeks to contribute to critical peace and conflict studies by (re)turning the local turn to local scholars who come from conflict-affected societies and who have themselves experienced the transition from war to peace. This book is essential reading for students and scholars of peace- and state-building, conflict studies and international relations